Nazi rule in Poland 1939-1945 - Cyprian, Tadeusz; Sawicki, Jerzy (Warsaw : Polonia, 1961)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Wereldoorlog 2; oorlogsmisdaden; jodenvervolging; Polen